SYSTEMATIC MANAGEMENT OF DIGITAL EDUCATION SERVICES IN ISLAMIC SENIOR HIGH SCHOOLS - Hamdani Fajar Apriwulan; Deny Hadi Siswanto; M.M. Endang Susetyawati; Eka Hidayati (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
This study aims to provide an in-depth description of digital-based educational service management at SMA Muhammadiyah Mlati, covering both academic and non-academic aspects. The research employed a descriptive qualitative approach, with data collected through in-depth interviews, direct observations, and documentation involving the principal, vice principal for curriculum affairs, teachers, administrative staff, and school operators. Data analysis was conducted using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing, with validity ensured through source and method triangulation. The findings indicate that digital service management at SMA Muhammadiyah Mlati is implemented systematically through stages of planning, organizing, implementation, and evaluation. In the academic aspect, programs such as ASBK, UASBK, and the digital library operate effectively through structured task organization based on official decrees and the use of e-learning platforms. Meanwhile, non-academic services such as Dapodik, ARKAS, and Online Student Admission enhance administrative efficiency. The main challenge lies in teachers’ adaptation to technology; however, the school’s support through continuous training, technical assistance, and the provision of classroom operators has successfully improved digital competence and the overall effectiveness of digital-based educational service management.